2004
DOI: 10.1017/s1367943004001337
|View full text |Cite
|
Sign up to set email alerts
|

Size matters: the value of small populations for wintering waterbirds

Abstract: Protecting systematically selected areas of land is a major step towards biodiversity conservation worldwide. Indeed, the identification and designation of protected areas more often than not forms a core component of both national and international conservation policies. In this paper we provide an overview of those Special Protection Areas and Ramsar Sites that have been classified in Great Britain as of 1998/99 for a selection of wintering waterbird species, using bird count data from the Wetland Bird Surve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…For example, despite relatively low species richness, areas of salt marsh provide sinks for pollution, protection against floods, and nurseries for commercially important fish species (Costanza et al 1997). In addition, the extensive coverage of estuarine and coastal areas within statutory protected areas means that a large proportion of the feeding and roosting areas regularly required by internationally important numbers of waterbirds overwintering in Britain (Jackson et al 2004b) are, to some extent at least, protected. Nonetheless, despite a greater number of sites and the prevalence of coastal areas, the average size of sites in lowland areas is much smaller when compared with those in upland areas.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, despite relatively low species richness, areas of salt marsh provide sinks for pollution, protection against floods, and nurseries for commercially important fish species (Costanza et al 1997). In addition, the extensive coverage of estuarine and coastal areas within statutory protected areas means that a large proportion of the feeding and roosting areas regularly required by internationally important numbers of waterbirds overwintering in Britain (Jackson et al 2004b) are, to some extent at least, protected. Nonetheless, despite a greater number of sites and the prevalence of coastal areas, the average size of sites in lowland areas is much smaller when compared with those in upland areas.…”
Section: Discussionmentioning
confidence: 99%
“…In practical terms, given that almost any parcel of land in the United Kingdom can potentially receive some level of protected status, the a priori expectation is that the extreme bias in the representation of environmental variation, land cover, or biodiversity features, as reported for various other countries, would not prevail. The few studies that have been conducted provide some evidence to the contrary (Hopkinson et al 2000, Jackson et al 2004b, Oldfield et al 2004). However, these analyses have been constrained in a number of important ways, including in their spatial scale (coarse resolution and/or narrow spatial extent), the protected area types considered (one or two different protected area categories only), and the range of environmental/ biological variables considered.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Meghalaya state, India: Khan et al 1997 ;Québec, Canada: Sarakinos et al 2001 ). In their review of this literature, Jackson et al ( 2004 ) concluded that most studies reported that the largest problems were insufficient coverage, sub-optimal species/ habitat representation and inadequate selection methods. For the Black-tailed Godwit in the Netherlands, selection of SPAs seems to have been inadequate for the important breeding population due to the criteria applied.…”
Section: Network Performancementioning
confidence: 99%
“…Waterbirds are among the most well-studied of animal groups, and several monitoring methods have been developed involving large numbers of volunteers in several long-term annual programmes (Bibby et al 1992, Wetlands International 2006. Wintering waterbirds often occur in spectacular concentrations while using a limited network of sites, the proper identification and protection of which has proved to be an effective conservation mechanism for many waterbird species (Jackson et al 2004b). Moreover, waterbirds are recognized as indicators of the richness and diversity of wetland ecosystems (Bibby et al 1992).…”
mentioning
confidence: 99%